SERRE WEIGHTS AND WILD RAMIFICATION IN TWO-DIMENSIONAL GALOIS REPRESENTATIONS - LASSINA DEMBÉLÉ; FRED DIAMOND; DAVID P. ROBERTS (Forum of Mathematics, Sigma, 2016)
A generalization of Serre’s Conjecture asserts that if